ANTIDIABETIC ACTIVITY OF GUANIDINIUM SALT 2-AMINOPHENYLACETATE - E. V. Ponomarenko (Разработка и регистрация лекарственных средств, 2019)
The purpose of the real research was studying of antidiabetic activity of new products of organic synthesis - guanidinium salt 2-aminophenylacetate. It was detected a pronounced hypoglycemic effect of the compounds when administered in intact animals and animals with alloxan diabetes model, and shows that the studied compound exhibits antiadrenergic effect and potentiates the effect of exogenous insulin.